IMPLEMENTASI KURIKULUM MUATAN LOKAL KEAGAMAAN DALAM PEMBENTUKAN BUDAYA RELIGIUS DI SMPN 2 NGORO JOMBANG - Hubaidi ilmuna; Khoirul Anwar (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2022)
This study aims to determine how the local content curriculum of religion is implemented in shaping religious culture. Through local content learning, religion can improve the quality of religion and develop students' cognitive and psychomotor values. This research is a case study using a qualitative approach. Meanwhile, judging from the data collection techniques in this study using the techniques of observation, interviews and documentation. While the data analysis technique used is a qualitative descriptive analysis technique. The results of research conducted by researchers related to the application of local content of religious programs in the formation of religious culture in SMP Negeri 2 Ngoro Jombang, indicate that the implementation of local content as part of the religious program at SMP Negeri 2 Ngoro Jombang is ongoing. . in 3 years. Teaching materials in the local religious content program are more focused on materials that develop students' religious abilities. The material taught includes the fields of prayer, reading and writing the Qur'an, worship and prayer, and memorizing letters. The formation of religious culture at SMP Negeri 2 Ngoro Jombang through various ways, including through school policies in the form of religious regulations and curriculum, as well as maximizing the function of religious institutions, religious icons. The development of a local content curriculum for religion by SMP Negeri 2 Ngoro which aims to form a religious culture in schools is reflected in the religious application program. This program is the result of extracurricular development in the curriculum of local religious content. In addition, teachers also develop learning outcomes or learning outcomes for local religious content.